2021
DOI: 10.4155/fmc-2021-0022
|View full text |Cite
|
Sign up to set email alerts
|

Computational Drug Repositioning for Ischemic Stroke: Neuroprotective Drug Discovery

Abstract: Background: A comprehensive approach to drug repositioning will be required to overcome translational hurdles and identify more neuroprotective drugs. Results & methods: Gene Set Enrichment Analysis was applied to identify related pathways and enriched genes. Candidate genes were optimized using ToppGene, ToppGenet and pBRIT. From the perspective of the local structures, gene–domain–substructure–drug relationships were constructed. Using the MCODE algorithm and K-means clustering, 31 functional subnetworks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…CCR5 inhibitors were also considered to be potentially repurposed for stroke recovery [8] . Li et al has utilized the computational drug repositioning approach for IS and identified 252 drugs with potential neuroprotective effects [9] . Moreover, as a peroxisome proliferator-activated receptor gamma and cannabinoid receptor type 2 dual agonist, VCE-004.8 has shown the possibility of repurposing its use as a delayed treatment option for IS [10] .…”
Section: Introductionmentioning
confidence: 99%
“…CCR5 inhibitors were also considered to be potentially repurposed for stroke recovery [8] . Li et al has utilized the computational drug repositioning approach for IS and identified 252 drugs with potential neuroprotective effects [9] . Moreover, as a peroxisome proliferator-activated receptor gamma and cannabinoid receptor type 2 dual agonist, VCE-004.8 has shown the possibility of repurposing its use as a delayed treatment option for IS [10] .…”
Section: Introductionmentioning
confidence: 99%